Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Cafe Man'A Garut - Muhammad Galih Maulana; Reza Suprimansyah; Tedi Rahmat Jaelani (Jurnal Manajemen dan Pemasaran, 2024)
The needs and lifestyles of Indonesians are increasingly diverse along with the progress that occurs in the current era of globalization. Indonesians crave food and beverages, which can be obtained by cooking or making them themselves. In the past, people preferred to eat out, either at restaurants or cafes, but now they prefer to complete tasks, gather with colleagues, and do other things. Cafes have now become a product brought about by modernity and have become an option as part of people's lifestyle. At the beginning of its emergence, cafe culture was considered to be an exclusive lifestyle of community activities, with only the wealthy group of people being able to do activities there. which is really cheaper. However, and this is something that some people prefer, many cafes offer high quality services to attract customers. Service quality is closely related to customer satisfaction. The level of satisfaction is calculated as a function of the difference between perceived performance and expected performance. Factors that contribute to improving service quality should also be considered. These include improving the skills of technical employees, talking to operational personnel directly about customer needs, or learning about management perspectives to reduce discrepancies. For the company to survive, service quality must be considered and maximized. Keywords: Service Quality, Customer Satisfaction